A NEW SPECIES OF NEPENTHES (NEPENTHACEAE) AND ITS NATURAL HYBRIDS FROM ACEH, SUMATRA, INDONESIA - Malcolm Victoriano (Research Center for Biology, 2021)
VICTORIANO, M. 2021. A new species of Nepenthes (Nepenthaceae) and its natural hybrids from Aceh, Sumatra, Indonesia. Reinwardtia 20(1): 17–26. — A new species of Nepenthes (Nepenthaceae) from Aceh Province, Indonesia, Nepenthes longiptera Victoriano is herein described and illustrated. The species is unique among all other Nepenthes in Sumatra by the presence of wings on its upper pitchers. Comprehensive description, photographs, geographical distribution and preliminary IUCN conservation assessment are provided for the new species. Hybrids of this new taxon with other species are also reported in this paper.